Implementasi Penanganan Pengaduan dalam Aplikasi SP4N-Lapor pada Dinas Perumahan, Permukiman, Cipta Karya, dan Tata Ruang - Ferronsyah, Bima (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The research was conducted to determine the implementation of complaint management in the SP4N-Lapor application at the Dinas Perumahan, Permukiman, Cipta Karya, dan Tata Ruang Kabupaten Sidoarjo. Research and data collection were carried out using descriptive qualitative methods, with a purposive sampling model. The theory used to analyze and process data is Van Meter and Van Horn's policy implementation model in which there are 6 aspects, namely; Standards and Objectives, Resources, Communication, Implementer Disposition, Implementer Character, and Environmental Conditions. The results showed that the implementation of complaints management in the SP4N-Lapor application in the OPD as the research locus had been carried out quite well, although there were still some minor notes and suggestions such as in the Resources aspect, especially in Human Resources. The rest of the remaining aspects only need to be maintained or improved. Then there needs to be a joint commitment and good communication that is established regularly for optimal and quality services in the future.